Analisis Perbandingan Profitabilitas PT. Unilever Indonesia TBK Sebelum dan Saat Isu Boikot Periode Tahun 2021–2024 - Eva Ananda Putri (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This study examines the comparative profitability of PT Unilever Indonesia Tbk before and during the boycott issue that emerged as part of the Boycott, Divestment, and Sanctions (BDS) movement in 2023. Profitability was selected as the focus because it is a key financial performance indicator that reflects the company’s ability to generate returns under changing social and economic pressures. The research aims to evaluate differences in financial performance using three indicators: Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM) across two periods, namely before the boycott (2021–2022) and during the boycott (2023–2024). Employing a quantitative descriptive-comparative approach, the study analyzed financial ratios and applied the Wilcoxon Signed-Rank Test. The findings reveal a decline in ROA from 30.20% (2021) and 29.29% (2022) to 28.81% (2023) and 20.99% (2024), as well as a drop in NPM from 14.56% and 13.02% to 12.49% and 9.59% during the boycott period. Conversely, ROE increased to 156.74% in 2024, largely driven by a sharper decline in equity compared to net profit. Nevertheless, statistical testing indicates no significant difference in profitability between the two periods. These results suggest that while profitability trends weakened, the boycott had no statistically significant impact, implying that investor and consumer responses were not strong or sustained enough to materially affect financial performance.